EFEK HIPOURISEMIA EKSTRAK ETANOL AKAR TUMBUHAN TUNJUK LANGIT (Helminthostachys zaylanica Linn Hook) TERHADAP MENCIT JANTAN GALUR SWISS - Fitrya Fitrya; Muharni Muharni (Majalah Obat Tradisional, 2014)
Tunjuk langit (Helminthostachys zeylanica) rhizome has been used as traditional medicines. i.e. anticancer and antiinflammation. Other studies revealed that the rhizome of tunjuk langit has antioxidant, anticancer, neuroprotective and anti-inflammatory effects. The main purpose of this research is to understand the hipouricemia potency of ethanol extract of tunjuk langit compared to that of alopurinol. In this study, 50 mice were divided into 10 groups (n=5 per group). Group I: normal group (CMC-Na 0.5% with dose of 10 mL/kg BB), Group II : negative control, Group III-VI : positive control (alopurinol with doses of 5, 10, 20 and 40 mg/kg BB) and VII-X : Ethanol extract with doses of 20, 40, 80, and 160 mg/kg BB. These groups were treated for 30 days. The uric acid level of their blood was measured on the day-0 and these groups were then inducted with a mixture of chicken liver juice (25 ml/kg BW 2 times/days) and  Gnetum gnemon seeds (2g/kg BW per day) from day-0 until day-30. The blood uric acid levels were measured on the 10th and 15th days. Extract tests were orally injected to the groups with each dose starting from the 15th day until 30th day. Meanwhile, chicken liver juice was also still given constantly within these days. The uric acid level and the percentage of its degradation of each group were measured on the 20th, 25th and 30th days. Based on the in vivo study, it could be concluded that the ethanol extract of Tunjuk langit has hipouricemia potency. The hipouricemia effects of ethanol extract with doses of 80 and 160 mg/kg BW are 91.95% and 91.77% compared to those of allopurinol with doses of 20 and 40 mg/kgBW, respectively. Based on relation between percentage of the degradation uric acid level and the extract concentration, ED50 value of the extract is 135.76 mg/kg BW.